Physician and professional caregiver perspectives on meaningful change in agitation behaviors in Alzheimer’s dementia: Insights from qualitative interviews - Smith, Jessica; Talon, Brian; Martinez, Ana; McCarrier, Kelly; Aggarwal, Jyoti (Frontiers in Dementia, 2025)
BackgroundAgitation is a common neuropsychiatric symptom of Alzheimer’s dementia. Limited qualitative evidence is available to characterize the clinical meaningfulness of changes in agitation behaviors, as assessed by the Cohen-Mansfield Agitation Inventory (CMAI).ObjectiveTo collect qualitative data to characterize the magnitude of change in CMAI scores required to represent a clinically meaningful improvement in agitation behaviors from the perspectives of physicians and professional caregivers.Materials and methodsOne-on-one qualitative interviews were conducted with 15 physicians treating Alzheimer’s dementia and 15 professional caregivers. Nine patient vignettes depicting observed changes in CMAI score profiles over a 12-week study period were used as examples of different magnitudes of change in the CMAI total score.ResultsThe proportion of participants affirming clinical meaningfulness varied for both physicians and caregivers within and across the nine vignettes presented; however, the four vignettes corresponding to a CMAI total score reduction of 14 or greater were considered clinically meaningful to all participants. Most physicians (8/13) and caregivers (7/13) found a total score reduction of 5 to be clinically meaningful, and some participants (2 caregivers; 0 physicians) articulated that even minimal changes could be clinically meaningful depending on the type of behavior.ConclusionParticipants who regularly treat people with Alzheimer’s dementia described a significant burden associated with agitation behaviors and provided qualitative examples highlighting that even minor reductions in the frequency of such behaviors can have meaningful benefits for the patient’s care and the burden on professional caregivers and family members.